Cold Plasma in Medicine and Healthcare: The New Frontier in Low Temperature Plasma Applications - Laroussi, Mounir (Frontiers in Physics, 2020)
Low temperature plasmas that can be generated at atmospheric pressure and at temperatures below 40 oC have in the past couple of decades opened up a new frontier in plasma applications: biomedical applications. These plasma sources produce agents, such as reactive species (radicals and non-radicals), charged particles, photons, and electric fields, which have impactful biological effects. Investigators have been busy elucidating the physical and biochemical mechanisms whereby low temperature plasma affects biological cells on macroscopic and microscopic scales. A thorough understanding of these mechanisms is bound to lead to the development of novel plasma-based medical therapies. This mini review introduces the reader to this exciting multidisciplinary field of research.